Pelatihan Penulisan Penelitian Tindakan Kelas Berbasis Teknologi Open Journal System dan Penggunaan Software R pada MGMP Matematika SMP - Muhammad Taqwa; Firdha Razak; Amrullah Mahmud (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Background: Mathematics Teachers who are members of MGMP (Teacher's Deliberation of Subjects) Mathematics at the Junior High School level of Pangkep Regency face problems in writing classroom action research (PTK), processing and analyzing data from PTK research results using software, as well as the publication of PTK scientific articles in the Open Journal System (OJS). The purpose to improve (1) the teacher's knowledge of the way of writing classroom action research (PTK); (2) the teacher's knowledge of software R statistical applications; (3) teacher knowledge of the Open Journal System (OJS). Method: Learning Model Technology, Pedagogy, and Content Knowledge (TPACK) consists of 4 steps: understanding (P), observation-instruction (O), instruction exercises (L), reflection (R). Training Partner is MGMP Mathematics junior high school pangkep which amounted to 12 people. Instruments of devotion in the form of: tests of classroom action research knowledge; test of software knowledge R; Open Journal System (OJS) knowledge test. Results: (1) increased teacher knowledge of how to write class actions; (2) increased teacher knowledge about processing classroom action research data with Software R; (3) Increased teacher knowledge about the publication of scientific articles of classroom action research in the Open Journal System (OJS). Conclusion: OJS Technology-Based PTK Training and The Use of Software R can overcome teacher difficulties in writing PTK, processing and analyzing PTK research data, as well as the publication of PTK scientific articles in the Open Journal System (OJS).